Unsustainable debt burden and poverty in Pakistan: A case for enhanced HIPC initiative - Tilat Anwar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The financing of Pakistan's substantial current account deficits within the framework of IMF and the World Bank structural adjustment programmes—about 6 per cent of GDP in the early 1990s led to a debt crisis in the late 1990s. IMF considered this level of current account deficit quite feasible in order to allow import liberalization, while the country needed both internal as well as the external adjustment. IMF also frequently demanded devaluation of the rupee against the US dollar to enhance exports. While exports remained stagnant, the devaluation has directly added to the rupee value of foreign debt resulting in a dramatic increase in debt service burden leading to debt crisis, lower economic growth and higher poverty level in 1998. While devaluation was supposed to boost exports and stimulate economic growth, it seems to have had a recessionary impact on the economy by raising the cost of imported intermediate inputs. Thus, devaluation as an instrument for export promotion involves substantial costs while its benefits are uncertain. Pakistan's external debt as per cent of GNP is now higher than all but the heavily indebted poor countries (HIPCs); its total debt service as per cent of exports is considerably higher than all the countries, including the HIPCs, a reflection of the country's grave debt crisis. Although Pakistan qualifies for assistance under the enhanced HIPC Initiative as per criterion of NPV of debt to exports, it has to strive to meet other eligibility criteria. This criteria should be revised to broaden the debt relief to countries whose debt problems are much severe than the HIPC countries. Countries like Pakistan with poverty reduction strategies should be entitled to immediate debt relief. For effective debt management, fiscal consolidation, including tax reform to strengthen the fiscal payments capacity, is essential in achieving debt sustainability. Attention should be given to eliminating the dependence on a very narrow production and export base. – debt ; adjustment ; poverty ; liberalization
Keywords: O11; F34; 330; Auslandsverschuldung; Anpassungsprogramm des IWF; Armut; Pakistan